Education on the Importance of Breast Milk and Complementary Foods for Breast Milk (MPASI) as an Effort to Prevent Stunting - Louisa Ariantje Langi; Fri Rahmawati; Ida Bagus Eka Utama Wija; Ganda Pariama; Nia Reviani (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Stunting is a form of growth failure (growth faltering) due to the accumulation of nutritional deficiencies that last for a long time starting from pregnancy until the age of 24 months. Optimal nutritional intake for newborns by providing exclusive breast milk as the main food until the age of 6 months and then continuing until the age of 2 years accompanied by appropriate and high-quality complementary foods will prevent stunting in toddlers. One important effort to prevent stunting is by empowering the community, especially parents, to pay attention to the intake of breast milk and complementary foods for their babies. By providing knowledge to the public about the importance of correct breastfeeding and MPASI, it is hoped that the public can change their behavior to prioritize exclusive breastfeeding and correct MPASI. This community service method uses an educational approach through outreach with a total of 139 participants who live in five villages in Jatigede District, Sumedang Regency, West Java. Socialization involving experts gave results that there was an increase in participants' knowledge as measured using pre-test and post-test instruments. The percentage of participants who experienced an increase in knowledge from 139 participants, the results obtained were 118 participants (85%) experienced an increase in knowledge about breast milk and complementary foods, and 19 people (14%) had the same knowledge before and after socialization while 2 people (1%) gained The score decreased during the post-test due to several factors, including some participants who did not have time to complete the post-test questionnaire due to having to do other work